Comparing oral health behaviours of men and women in the United States. (July 2022) - Su, Sharon; Lipsky, Martin S.; Licari, Frank W.; Hung, Man
Abstract: Objective: This study used a national database to update and examine current differences in men's and women's oral health and oral health behaviours in the United States. Methods: Data from the National Health and Nutrition Examination Survey for the 2017–2018 cycle were used to explore the relationship between males and females and their oral health. Multivariate analyses assessed for gender differences in oral health behaviors between genders after controlling for sample demographic characteristics. Results: The final sample consisted of 4, 741 participants. Males tended to have fewer dental visits, worse perception of their gum and tooth health, poorer flossing habits, and more root caries. Females were more proactive in visiting dentists and displayed a greater awareness of oral health. Females were less likely to report discussing oral cancer screening with their dentist even though they were screened more often. On examination, males were more often advised to seek urgent dental care than females. All these differences were statistically significant at p <0.05, although the effect size for examination variables was small (Phi <0.1). Conclusions: Oral health and oral health behaviours demonstrate gender differences with men reporting poorer oral health, poorer oral hygiene habits, and fewer dental visits. These findings suggest gender-targeted strategies have the potential to improve oral health and reduce gender-related disparities. Clinical Significance: This study found that women exhibit better oral health practices and behaviours. These differences may cause a disproportionate burden of oral disease in men and highlight the need for dentists, hygienists, and those interested in dental public health to develop gender-specific strategies to address these inequalities.